A Handbook of Qualitative Methodologies for Mass Communication Research - Klaus Bruhn Jensen , Nicholas W.Jankowski (Routledge, 2002)
The publication of this Handbook marks the culmination of several professional and personal itineraries. The chapters of the volume suggest that the field of mass communication research has been undergoing two interrelated developments in recent decades: the rise of qualitative approaches as methodologies with an explanatory value in their own right, and the convergence of humanistic and socialscientific disciplines around this â€œqualitative turn.â€ As editors, we offer the Handbook as a resource for the further development and social use of qualitative methodologies in different cultural and institutional contexts. The personal itineraries have taken one editor from Europe to the United States, the other from the United States to Europe, and both to India, where the idea for the Handbook was first conceived during the 1986 meeting of the International Association for Mass Communication Research. As participants in this conference, we were reminded repeatedly that while qualitative research represented an important (and frequently the most inspiring) part of the scholarship presented at that and similar events, there were as yet hardly any journals, conference sessions, or handbooks available which could serve to institutionalize this area of inquiry and to introduce students and young researchers to its methodologies. The cultural setting of the 1986 conference also contributed to our awareness that for the study of communication in its varied social and cultural contexts to become valid or meaningful, methods of qualitative and â€œthickâ€ description (Geertz, 1973) are required.